Characteristics of Hypertension Patients at the Mowewe Community Health Center, East Kolaka Regency - Reskia Arlinda Bustanil; Nur Anisa; Maemuna (Journal of Epidemiology and Health Science, 2026)
Background: Hypertension is a non-communicable disease whose incidence continues to increase, both globally and in Indonesia. This condition poses a serious challenge to public health because it is often not detected early. Many sufferers are unaware that their blood pressure has increased to the point of eventually causing various complications. This has led hypertension to be nicknamed the silent killer because it can lead to serious disorders such as stroke, heart disease, and kidney dysfunction without obvious symptoms. Objective: This study aims to describe the characteristics of hypertension patients based on age, gender, and occupation in the work area of the Mowewe Health Center, Kolaka Regency in 2024. Methods: This study uses a descriptive method with a quantitative approach. Secondary data was obtained from the medical records of hypertension patients at the Mowewe Health Center in 2024 as many as 166 samples. The analysis was conducted to describe the distribution of cases based on the study variables. Results: The results showed that the age group with the most hypertension was 45–54 years old (26.5%). Based on gender, the majority of people with hypertension are women (94.6%). Based on employment, most of the sufferers are housewives (48.2%), followed by the self-employed (18.7%) and civil servants (17.5%). Conclusion: The incidence of hypertension in the work area of the Mowewe Health Center tends to increase in middle age and the elderly, is more experienced by women, and is highest in the group of housewives. Risk factors that play a role include degenerative processes due to aging, stress, lack of physical activity, and an unbalanced diet. Keywords: Aged, Hypertension, Incidence, Occupation, Risk factors.